2010
DOI: 10.1007/s00256-010-1022-1
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic evaluation of the xiphoid process with 64-row multidetector computed tomography

Abstract: Significant interindividual variations were detected in the xiphoid process. Excellent anatomic evaluation capacity of MDCT facilitates the detection of variations of the xiphoid process as well as the whole ribcage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 9 publications
0
38
0
2
Order By: Relevance
“…The direction, calcification, and termination of the XP and the developmental variations in the XP were evaluated. Ventral deviation occurred more frequently in previous studies (21). In our study, ventral deviation was observed in 135 cases, and no deviation was observed in 115 cases.…”
Section: Discussionmentioning
confidence: 50%
“…The direction, calcification, and termination of the XP and the developmental variations in the XP were evaluated. Ventral deviation occurred more frequently in previous studies (21). In our study, ventral deviation was observed in 135 cases, and no deviation was observed in 115 cases.…”
Section: Discussionmentioning
confidence: 50%
“…Babinski et al [5] reported a higher prevalence of 16.6%. Akin et al [10] Determined that xiphoidal foramen was present in 216 patients (43.2%); 171 patients (34.2%) had only one foramen; 31 patients (6.2%) had two, seven patients (1.4%) had three, and seven patients (1.4%) had four or more xiphoidal foramina. Prevalence of sternal foramen features an important correlation with the sex.…”
Section: Discussionmentioning
confidence: 99%
“…Radiologists and pathologists should be aware of the existences of these anatomical variations of the sternum as well as be familiar with their imaging features, in order to avoid diagnosis uncertainties [8,21]. [10] studied interindividual variations of the xiphoid process in a wide adult group using 64-row multidetector computed tomography (MDCT). They found that the mean length and the thickness of xiphoid process had been 50 mm and 7.3 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports on the postnatal development of the human sternum were not thoroughly analyzed with histological methods but rather with radiographic methods. Much previous literature reports that human xiphoid process has a high degree of individual variation [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%